Methods of Portraiture in the Process of Making Sketches and Drawings of the Human Face in Higher Pedagogical Education - Botir Boltaboevich , Baymetov (International Journal of Psychosocial Rehabilitation, 2020)
This article provides methodological guidelines for the correct depiction of the human in the professional training of future teachers of fine arts in higher pedagogical education. Attention is also paid to the development of continuous academic image processing skills through the acquisition by students of the formation of constructive construction skills, which are the basis for image performance.